An inner wall conductive transparent glass electron beam tube and a method for manufacturing the same

CN122991933APending Publication Date: 2026-10-27HUNAN FIRST NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611468871.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明所要解决的技术问题在于,提供一种内壁导电透明玻璃电子束管及其制备方法,能够解决现有物理气相沉积、电镀等方法在细长玻璃管内壁镀膜不均匀、附着力弱、成分厚度难以控制,以及原子层沉积无法实现仅内壁镀膜、外壁绝缘的问题

Benefits of technology

(1)本发明采用原子层沉积共沉积技术制备铝掺杂氧化锌透明导电薄膜,原子层沉积属于化学生长,氧化物前驱体与基底表面羟基发生化学反应而形成致密牢固的薄膜,薄膜与基底为化学键结合,附着力明显强于物理气相沉积方法所沉积的薄膜,能够承受高速运动电子束的撞击;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991933A_ABST
    Figure CN122991933A_ABST
Patent Text Reader

Abstract

The application discloses an inner-wall conductive transparent glass electron beam tube and a preparation method thereof. The method comprises the following steps: cleaning the transparent glass tube to be coated; winding a metal foil around the outer wall of the transparent glass tube and fixing the metal foil with a fixing ring to form a metal foil winding cylinder shielding the outer wall; placing the assembly to be coated in a constant temperature zone of a tubular heating furnace, making a precursor guide into the winding cylinder and keeping a distance with the inner wall of the tube; alternately inputting a zinc source precursor, an oxidizing agent and an aluminum source precursor under atomic layer deposition conditions to form one super cycle with X zinc oxide cycles and Y aluminum oxide cycles, repeating N times to deposit an aluminum-doped zinc oxide transparent conductive film on the inner wall of the tube, and obtaining the inner-wall conductive and outer-wall insulated electron beam tube. The application realizes uniform film forming on the inner wall of the slender glass tube and accurate control of the composition and thickness by the shape retention and self-limiting property of atomic layer deposition, and the resistance of the two ends of the tube can be adjusted to the required interval through the cycle ratio and the super cycle number.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vacuum electronic devices and thin film fabrication technology, and in particular to an inner wall conductive transparent glass electron beam tube and its fabrication method. Background Technology

[0002] The conductive transparent glass electron beam tube is a specially designed vacuum electronic device. Its core feature is the use of a transparent glass tube with a conductive inner wall and an insulated outer wall as its main structure. Its main characteristics include: First, optical transparency: the transparent glass tube wall allows direct observation of the working status of the internal components, the light spots generated by the electron beam bombarding the fluorescent screen, or gas discharge phenomena, facilitating experimental observation, equipment debugging, or special display purposes. Second, conductive inner wall: the conductive layer on the inner wall effectively dissipates any charge that may accumulate on the tube wall, preventing electron beam defocusing, drift, or image distortion caused by static electricity accumulation. Simultaneously, this conductive layer can serve as part of the electrodes, participating in the construction or optimization of the electric field distribution within the tube. Third, external wall insulation for safety: the external insulation ensures the safety of operators and prevents accidental electrical connections or short circuits caused by the conductive outer shell when the device is installed in circuits or equipment. Its main applications include special display and observation equipment, scientific instruments requiring simultaneous electrical signal control and optical observation, and dedicated oscilloscopes, playing an important role in some special photoelectric conversion and detection applications.

[0003] Electron beam tubes with conductive transparent glass inner walls place higher demands on the conductive coating: controllable resistance at both ends of the electron beam tube, strong adhesion of the conductive layer, and the ability to withstand the impact of high-speed electron beams are typically required. To ensure the transparency of the electron beam tube, the selected coating is usually a multi-element transparent conductive material such as ITO, FTO, AZO, or IZO. This device is typically a slender tubular structure, reaching hundreds of millimeters in length and approximately 10–30 millimeters in inner diameter, representing a typical high aspect ratio structure. Uniform coating on its inner wall is a key challenge in the fabrication process.

[0004] Conductive coating technology for the inner walls of micropores or complex structures is a key process in microelectronics and precision manufacturing, currently mainly achieved through methods such as physical vapor deposition (PVD) and electroplating. Ion beam deposition uses an ion emission source to generate an ion beam in a vacuum environment. The electric fields of the focusing and accelerating electrodes control the ions to enter the micropores and deposit them on the inner walls to form a conductive film. However, this method has planar characteristics, making it difficult to form a uniform coating on the inner walls of deep, long pipes hundreds of millimeters long with inner diameters of 10–30 millimeters. Sputtering deposition results in relatively low film-substrate adhesion, easily leading to uneven thickness and cracking or peeling due to stress accumulation on the inner walls of pipes with high aspect ratios. Evaporation deposition uses low-energy deposited particles, resulting in relatively weak film-substrate adhesion. Furthermore, the evaporating particles move in a straight line, making it difficult to uniformly cover complex structures such as steps and pores, causing uneven thickness. Electroplating requires a substrate with excellent conductivity, therefore it cannot be used to prepare conductive layers on the inner walls of insulating glass tubes.

[0005] Atomic layer deposition (ALD) is based on alternating precursor pulses and self-limiting surface reactions. It can be used to deposit conductive thin films such as aluminum-doped zinc oxide and indium-doped tin oxide. These films offer advantages such as strong adhesion, density, and precise control over thickness and composition. There have been some reports on the deposition of transparent conductive films on planar substrates. However, successful applications of ALD in coating the inner walls of long, tubular structures have not been reported, mainly due to multiple technical limitations in ALD equipment and processes. Furthermore, ALD deposits films on all exposed surfaces; without shielding the outer wall of the glass tube, conductive films will be deposited on both the inner and outer walls, resulting in conductivity on the outer wall and compromising the required external wall insulation properties of electron beam tubes.

[0006] Therefore, there is an urgent need for a method to prepare an inner-wall conductive transparent glass electron beam tube that can uniformly form a film on the inner wall of a slender transparent glass tube, with strong film adhesion, precise control of composition and thickness, and ensure insulation of the outer wall. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide an inner wall conductive transparent glass electron beam tube and its preparation method, which can solve the problems of uneven coating, weak adhesion, and difficulty in controlling composition and thickness on the inner wall of slender glass tubes by existing physical vapor deposition, electroplating and other methods, as well as the inability of atomic layer deposition to achieve coating only on the inner wall and insulation on the outer wall.

[0008] To address the aforementioned technical problems, the first aspect of this invention discloses a method for preparing an inner-walled conductive transparent glass electron beam tube, comprising the following steps: S1. Place the transparent glass tube to be coated in acetone, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning, each time for 10 to 20 minutes. After removal, dry at 80 to 120°C. S2. A metal foil is wound and wrapped around the outer wall of the transparent glass tube to form a metal foil winding cylinder. The inner wall of the metal foil winding cylinder is in close contact with the outer wall of the transparent glass tube, and the axial length of the metal foil winding cylinder is greater than the axial length of the transparent glass tube. Fixing rings are respectively provided on the outer periphery of the metal foil winding cylinder at both ends of the transparent glass tube to fix the transparent glass tube and the metal foil winding cylinder, thereby obtaining the component to be plated. S3. Place the component to be plated in the constant temperature zone of the tubular heating furnace, so that the precursor inlet tube of the atomic layer deposition equipment extends into the metal foil winding cylinder, and maintain a distance of 20-50mm between the outlet end of the precursor inlet tube and the inner wall of the transparent glass tube. S4. Under atomic layer deposition conditions, zinc source precursor and oxidant are sequentially cyclically introduced to deposit zinc oxide, and aluminum source precursor and oxidant are introduced to deposit aluminum oxide. X zinc oxide deposition cycles and Y aluminum oxide deposition cycles constitute a supercycle, where X and Y are both positive integers. The supercycle is repeated N times to deposit an aluminum-doped zinc oxide transparent conductive film on the inner wall of the transparent glass tube, resulting in the inner wall conductive transparent glass electron beam tube, where N is a positive integer. During the deposition process, the metal foil winding cylinder prevents the precursor from contacting the outer wall of the transparent glass tube, keeping the outer wall of the transparent glass tube insulated.

[0009] As an optional implementation, in the first aspect of the present invention, in step S4, the Al / (Zn+Al) cycle ratio of the aluminum-doped zinc oxide transparent conductive film is 0.024 to 0.091, preferably 0.04 to 0.048; the cycle ratio is the ratio of the number of alumina deposition cycles to the sum of the number of zinc oxide deposition cycles and the number of alumina deposition cycles.

[0010] As an optional implementation, in the first aspect of the present invention, in step S4, Y is 1, X is 5 to 20, and N is 4 to 45; more preferably, X is 11 and N is 9 to 21.

[0011] As an optional implementation, in the first aspect of the present invention, in step S4, the deposition temperature is 200-300°C; the single-cycle growth rate of the zinc oxide is 0.22 nm / cycle, the single-cycle growth rate of the aluminum oxide is 0.12 nm / cycle, and the thickness of the aluminum-doped zinc oxide transparent conductive film is determined by the single-cycle growth rate and the total number of deposition cycles.

[0012] As an optional implementation, in the first aspect of the present invention, in step S4, the zinc source precursor is diethylzinc, the aluminum source precursor is trimethylaluminum, the oxidant is water, the pulse introduction time of each precursor is 0.1 to 1 s, the adjacent pulses are purged with nitrogen for 2 to 10 s, and the reaction chamber pressure is maintained at 100 to 500 Pa during the deposition process.

[0013] As an optional implementation, in the first aspect of the present invention, in step S2, the metal foil is an aluminum foil with a thickness of 0.4 to 0.6 mm; the fixing ring is two aluminum rings, the inner diameter of the aluminum rings is adapted to the outer diameter of the transparent glass tube, and the ring width is 8 to 15 mm, respectively fitted inside the metal foil winding cylinder near both ends of the transparent glass tube.

[0014] As an optional implementation, in the first aspect of the present invention, in step S1, the transparent glass tube is a quartz tube with a length of 100-500 mm, an inner diameter of 10-30 mm, and a wall thickness of 0.5-3 mm.

[0015] The second aspect of the present invention discloses an inner wall conductive transparent glass electron beam tube, which is prepared by any of the preparation methods described in the first aspect of the present invention; the inner wall of the electron beam tube is provided with an aluminum-doped zinc oxide transparent conductive film, the outer wall is insulated, and the resistance between the two ends of the electron beam tube is 0.8kΩ to 156.2kΩ.

[0016] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: (1) The present invention uses atomic layer deposition co-deposition technology to prepare aluminum-doped zinc oxide transparent conductive film. Atomic layer deposition is a chemical growth process. The oxide precursor reacts chemically with the hydroxyl groups on the substrate surface to form a dense and firm film. The film and the substrate are chemically bonded, and the adhesion is significantly stronger than that of the film deposited by physical vapor deposition method. It can withstand the impact of high-speed electron beams. (2) Atomic layer deposition is a surface-controlled vapor deposition method with good three-dimensional shape preservation. It can achieve uniform coating on the inner wall of a slender transparent glass tube with a length of several hundred millimeters and an inner diameter of 10 to 30 millimeters. It overcomes the defects of uneven coating thickness and easy cracking and peeling on the inner wall of tubular structures with high aspect ratio by ion beam focusing deposition, sputtering, evaporation and other methods. (3) The composition and thickness of aluminum-doped zinc oxide thin film can be precisely controlled: the aluminum doping concentration can be adjusted by adjusting the cycle ratio X:Y of zinc oxide and aluminum oxide in the supercycle, and the film thickness can be adjusted by adjusting the number of supercycles N. Thus, the conductivity of both ends of the transparent glass electron beam tube can be continuously adjusted, overcoming the limitations of physical vapor deposition method which depends on the target composition and one target can only correspond to one doping concentration. (4) In this invention, a metal foil winding cylinder is tightly wrapped around the outer wall of the glass tube and fixed with a fixing ring. During the deposition process, the precursor is prevented from contacting the outer wall of the glass tube, so that only the inner wall is coated with a conductive film and the outer wall remains insulated, which meets the safety insulation requirements of the outer wall of the electron beam tube. At the same time, the metal foil has good thermal conductivity, which improves the heating uniformity of the glass tube. (5) This invention provides the U-shaped variation of the resistance at both ends of the tube with the Al / (Zn+Al) cycle ratio and the variation of the resistance with the number of supercycles under the preferred cycle ratio. It provides a quantitative process window for the resistance design of the inner wall conductive transparent glass electron beam tube, and can stably prepare preferred devices with a resistance between 500Ω and 10kΩ. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram illustrating the principle of preparing aluminum-doped zinc oxide nanofilms by atomic layer deposition co-deposition as disclosed in the embodiments of the present invention; Figure 2 This is a schematic diagram of the chemical bonding between the aluminum-doped zinc oxide thin film and the substrate hydroxyl groups disclosed in the embodiments of the present invention; Figure 3 This is a schematic diagram of the atomic layer deposition equipment and sample clamping shielding structure applicable to the embodiments of the present invention; Figure 4 This is a graph showing the relationship between the resistance at both ends of the transparent glass electron beam tube in an embodiment of the present invention and the Al / (Zn+Al) cycle ratio; Figure 5 This is a graph showing the relationship between the resistance at both ends of the transparent glass electron beam tube and the number of supercycles under a preferred cycle ratio according to an embodiment of the present invention. Figure 6 This is a schematic diagram of the resistance measurement connection of the aluminum-doped zinc oxide inner wall conductive transparent glass electron beam tube prepared according to an embodiment of the present invention. Detailed Implementation

[0019] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1 See Figure 1This embodiment discloses a method for preparing an aluminum-doped zinc oxide inner-wall conductive transparent glass electron beam tube. The principle of preparing aluminum-doped zinc oxide nanofilms using atomic layer deposition (ALD) co-deposition technology is as follows: When depositing zinc oxide nanofilms alone, due to the self-limiting characteristics of ALD growth, the thickness of the deposited zinc oxide is approximately 0.22 nm / cycle, and the thickness of the zinc oxide film can be completely controlled by the number of ALD cycles; when depositing aluminum oxide films alone, the growth rate is approximately 0.12 nm / cycle, and the film thickness deposited in each cycle is close to one atomic layer, which is an atomically controllable fabrication method; by combining the above two ALD processes of zinc oxide and aluminum oxide, a supercycle is formed by X zinc oxide deposition cycles and Y aluminum oxide deposition cycles. By adjusting the cycle ratio X:Y, a compositionally controllable aluminum-doped zinc oxide nanofilm can be obtained. The conductivity of the zinc oxide nanofilm can be adjusted by changing the aluminum doping content and the film thickness.

[0021] See Figure 2 Atomic layer deposition growth is a type of chemical growth. Zinc oxide and aluminum oxide precursors react chemically with hydroxyl groups on the substrate surface to form a dense and strong film. The aluminum-doped zinc oxide film forms chemical bonds with the substrate and has excellent adhesion.

[0022] See Figure 3 The deposition equipment is a nanofilm preparation device compatible with atomic layer deposition and plasma chemical vapor deposition. The equipment includes a tubular furnace, a precursor inlet tube, a pulse valve, a precursor source bottle, a vacuum gauge, a baffle valve, and a vacuum pump. The precursor source bottles include a trimethylaluminum source bottle, a diethylzinc source bottle, and a water source bottle. Each precursor is alternately introduced through a pulse valve. The carrier gas and purge gas are nitrogen. The clamping method is as follows: the cleaned quartz tube to be coated is rolled into a cylindrical shape with 0.5 mm thick aluminum foil. The inner wall of the aluminum foil cylinder is tightly attached to the outer wall of the quartz tube, and the length of the aluminum foil cylinder is greater than the length of the quartz tube. Then, the quartz tube is fixed with two aluminum rings. The inner diameter of the aluminum rings is adapted to the outer diameter of the quartz tube, and the ring width is 8-15 mm. The aluminum foil cylinder prevents the rolled aluminum foil from unwinding and ensures that the inner wall of the aluminum foil cylinder is tightly attached to the outer wall of the quartz tube, thereby preventing the precursor from contacting the outer wall of the quartz tube during the deposition process. At the same time, the aluminum foil has good thermal conductivity, which can improve the heating uniformity of the quartz tube. Then, the wound and fixed samples are placed into the quartz tube heating furnace and placed in the middle constant temperature zone of the quartz tube heating furnace. The precursor inlet tube extends into the aluminum foil winding cylinder, and its outlet end is kept 20-50 mm away from the inner wall of the quartz tube to be coated, to ensure that the precursor reaction source can smoothly enter the quartz tube to be coated and react chemically with the inner wall of the tube.

[0023] The specific process is as follows: S1. Clean and dry the transparent glass tube to be coated; S2. Wrap the tube with aluminum foil as described above and fix it with an aluminum ring to obtain the component to be coated; S3. Place the component to be coated in the constant temperature zone of the tubular heating furnace, with the precursor inlet tube extending into the aluminum foil winding cylinder and maintaining a distance from the inner wall of the glass tube; S4. At a deposition temperature of 250℃, using diethylzinc as the zinc source precursor, trimethylaluminum as the aluminum source precursor, water as the oxidant, and nitrogen as the purge gas, pulse the pulses of each precursor. The injection time is 0.1–1 s, the purge time between adjacent pulses is 2–10 s, and the reaction chamber pressure is maintained at 100–500 Pa. Zinc source precursor and oxidant are sequentially introduced to deposit zinc oxide, and aluminum source precursor and oxidant are introduced to deposit aluminum oxide. X zinc oxide deposition cycles and Y aluminum oxide deposition cycles constitute a supercycle. The supercycle is repeated N times to form an aluminum-doped zinc oxide transparent conductive film on the inner wall of the transparent glass tube, resulting in a transparent glass electron beam tube with conductive inner wall and insulating outer wall.

[0024] The single-cycle thin film growth rates for atomic layer deposition of zinc oxide and aluminum oxide at 250°C were 0.22 nm / cycle and 0.12 nm / cycle, respectively. Therefore, the film thickness can be estimated based on these growth rates, cycle ratios, and supercycle numbers. A transparent conductive electron beam tube with a length of 200 mm, an inner diameter of 12 mm, and an outer diameter of 14 mm was prepared using the method of this embodiment.

[0025] Under the premise that the total number of atomic layer deposition cycles is basically the same, changing the Al / (Zn+Al) cycle ratio during the deposition process can yield inner-wall conductive transparent electron beam tubes with different conductivity properties. The data are shown in Table 1 and... Figure 4 As shown, when the Al cycle ratio increases from 0.024 to 0.091, the conductivity of the obtained electron beam tube exhibits a U-shaped trend, and the preferred cycle ratio for conductivity is 0.043.

[0026] Table 1. Relationship between resistance of transparent glass electron beam tube and Al / (Zn+Al) cycle ratio when the total number of cycles is constant.

[0027] By changing the supercycle number while keeping the preferred cycle ratio constant, thin films of different thicknesses can be deposited. See Table 2 and... Figure 5 As shown, the resistance across the electron beam tube decreases significantly as the number of supercycles increases from 4 to 7; when the number of supercycles increases from 9 to 21, the decreasing trend of the resistance across the electron beam tube slows down significantly, and the preferred resistance is between 500Ω and 10kΩ.

[0028] Table 2. Relationship between resistance and supercycle number of transparent glass electron beam tube under optimized cycle ratio conditions.

[0029] Figure 6 This diagram illustrates the resistance measurement connection of a transparent inner-wall conductive glass electron beam tube fabricated via atomic layer deposition (ALD). A digital multimeter was used to measure the resistance at both ends of the electron beam tube via alligator clips. In summary, the ALD co-deposition technique proposed in this embodiment achieves the deposition of aluminum-doped zinc oxide transparent conductive films. These films possess advantages such as strong adhesion, density, and precise controllability of thickness and composition. The conductivity at both ends of the transparent electron beam glass tube can be adjusted by regulating the ALD cycle ratio or the supercycle number, thereby fabricating the desired inner-wall conductive transparent electron beam tube.

[0030] Example 2 This embodiment discloses an inner-wall conductive transparent glass electron beam tube, prepared using the method described in Embodiment 1. The inner wall of the electron beam tube is provided with an aluminum-doped zinc oxide transparent conductive film, which is chemically bonded to the inner wall of the glass tube, resulting in a dense and uniform film layer. Due to the metal foil winding cylinder preventing the precursor from contacting the outer wall of the glass tube during deposition, the outer wall of the electron beam tube remains insulated, as measured by an insulation resistance tester. The electron beam tube has a length of 100–500 mm and an inner diameter of 10–30 mm; the resistance between its two ends is 0.8 kΩ–156.2 kΩ, preferably between 500 Ω and 10 kΩ. This conductive layer on the inner wall of the electron beam tube can conduct away the charge accumulated on the tube wall, avoiding electron beam defocusing, drift, or image distortion caused by electrostatic accumulation, and can also participate in constructing the electric field distribution inside the tube as part of the electrode; the outer wall insulation ensures operational safety, and the transparent tube wall allows direct observation of the electron beam's working state inside the tube.

[0031] The content disclosed in the embodiments of this invention is only a preferred embodiment of the invention and is used only to illustrate the technical solutions of the invention, not to limit it. Although the invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this invention.

Claims

1. A method for preparing an electron beam tube with an inner conductive transparent glass wall, characterized in that, Includes the following steps: S1. Place the transparent glass tube to be coated in acetone, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning, each time for 10 to 20 minutes. After removal, dry at 80 to 120°C. S2. A metal foil is wound and wrapped around the outer wall of the transparent glass tube to form a metal foil winding cylinder. The inner wall of the metal foil winding cylinder is in close contact with the outer wall of the transparent glass tube, and the axial length of the metal foil winding cylinder is greater than the axial length of the transparent glass tube. Fixing rings are respectively provided on the outer periphery of the metal foil winding cylinder at both ends of the transparent glass tube to fix the transparent glass tube and the metal foil winding cylinder, thereby obtaining the component to be plated. S3. Place the component to be plated in the constant temperature zone of the tubular heating furnace, so that the precursor inlet tube of the atomic layer deposition equipment extends into the metal foil winding cylinder, and maintain a distance of 20-50mm between the outlet end of the precursor inlet tube and the inner wall of the transparent glass tube. S4. Under atomic layer deposition conditions, zinc source precursor and oxidant are sequentially cyclically introduced to deposit zinc oxide, and aluminum source precursor and oxidant are introduced to deposit aluminum oxide. X zinc oxide deposition cycles and Y aluminum oxide deposition cycles constitute a supercycle, where X and Y are both positive integers. The supercycle is repeated N times to deposit an aluminum-doped zinc oxide transparent conductive film on the inner wall of the transparent glass tube, thereby obtaining the inner wall conductive transparent glass electron beam tube, where N is a positive integer; During the deposition process, the metal foil winding cylinder prevents the precursor from contacting the outer wall of the transparent glass tube, thus keeping the outer wall of the transparent glass tube insulated.

2. The preparation method according to claim 1, characterized in that, In step S4, the Al / (Zn+Al) cycle ratio of the aluminum-doped zinc oxide transparent conductive film is 0.024 to 0.091, where the cycle ratio is the ratio of the number of alumina deposition cycles to the sum of the number of zinc oxide deposition cycles and the number of alumina deposition cycles.

3. The preparation method according to claim 2, characterized in that, The cycle ratio is 0.04 to 0.

048.

4. The preparation method according to claim 1, characterized in that, In step S4, Y is 1, X is 5 to 20, and N is 4 to 45.

5. The preparation method according to claim 4, characterized in that, X is 11, and N is 9 to 21.

6. The preparation method according to claim 1, characterized in that, In step S4, the deposition temperature is 200–300°C; the single-cycle growth rate of the zinc oxide is 0.22 nm / cycle, the single-cycle growth rate of the aluminum oxide is 0.12 nm / cycle, and the thickness of the aluminum-doped zinc oxide transparent conductive film is determined by the single-cycle growth rate and the total number of deposition cycles.

7. The preparation method according to claim 1, characterized in that, In step S4, the zinc source precursor is diethylzinc, the aluminum source precursor is trimethylaluminum, the oxidant is water, the pulse introduction time of each precursor is 0.1 to 1 s, and the nitrogen is purged for 2 to 10 s between adjacent pulses. The pressure in the reaction chamber is maintained at 100 to 500 Pa during the deposition process.

8. The preparation method according to claim 1, characterized in that, In step S2, the metal foil is an aluminum foil with a thickness of 0.4 to 0.6 mm; the fixing ring consists of two aluminum rings, the inner diameter of which is adapted to the outer diameter of the transparent glass tube and the ring width is 8 to 15 mm, and they are respectively fitted into the metal foil winding cylinder near both ends of the transparent glass tube.

9. The preparation method according to claim 1, characterized in that, In step S1, the transparent glass tube is a quartz tube with a length of 100-500 mm, an inner diameter of 10-30 mm, and a wall thickness of 0.5-3 mm.

10. An electron beam tube with an inner conductive transparent glass wall, characterized in that, The electron beam tube is prepared by any one of the preparation methods described in claims 1 to 9; the inner wall of the electron beam tube is provided with an aluminum-doped zinc oxide transparent conductive film, the outer wall is insulated, and the resistance between the two ends of the electron beam tube is 0.8kΩ to 156.2kΩ.